Managing catastrophic loss of sensitive data a guide for IT and security professionals - Photopoulos, Constantine (Rockland, Mass. : Syngress ; Oxford : Elsevier Science [distributor], 2008)
Offering a structured approach to handling and recovering from a catastrophic data loss, this book will help both technical and non-technical professionals put effective processes in place to secure their business-critical information and provide a roadmap of the appropriate recovery and notification steps when calamity strikes. *Addresses a very topical subject of great concern to security, general IT and business management *Provides a step-by-step approach to managing the consequences of and recovering from the loss of sensitive data. *Gathers in a single place all information about this critical issue, including legal, public relations and regulatory issues.
Overview; Data Loss Consequences; Prevention and Protection; Data Loss Response Team; Detection; Analysis; Response; Notification; Legal Issues and Requirements; Lessons Learned; Appendix--Relevant Legislation.
Keywords: Emergency management; Data protection; Computer security; Electronic books